The Factors Influence Students’ Fears In Practicing English Conversation In Front Of Class - Joko Prayudha.S (Program Studi Tadris Bahasa Inggri Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Speaking skill is one of the most important skills in learning a language. This skill requires language learners to produce utterances or utterances through speech media. When someone studies a language, it is very necessary to be able to practice the pronunciation of that language so that they are able to produce a good language. Therefore, this study aims to analyze the factors that influence students' fear in practicing English conversation in front of the class when carrying out English learning. The method used in this research is qualitative by using a descriptive approach. The sample in this study were 36 students who were learning English. Data was obtained through observation and interviews to find out in-depth perceptions and opinions about the factors that make students feel afraid when carrying out conversational practice in front of the class. After the data is collected, the data is analyzed through three stages, namely data reduction, data display and conlusion. The research results show that there are two factors; internal and external influences that affect students' fear when practicing conversation in front of the class. Internal factors include not feeling confident, not daring, afraid of being wrong, embarrassed, not fluent in conveying an utterance, while external factors include an unsupportive classroom environment including distraction from friends, not having enough understanding of words or vocabulary in English, getting negative responses, for example being laughed at or ridiculed, and not having friends or partners to practice English conversation with.